More answers

c= -25

Q: C plus 11 equals -14

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

-14 + c + 6 = -5-14 + c = -5 minus 6-14 + c = -11c = -11 minus -14c = -11 plus 14c = 3

c plus 8 equals 11; now subtract 8 from both sides, then c=3.

a+b = 17a+c = 36 ----> c = 36 - ab+c = 25 ----> c = 25 - bSo since both are c, we say36 - a = 25 -bFrom this : 11 = a - bLook at 1st eqn: a + b = 17Now we have: a - b = 11 ----> a = 11 + bSo we can substitute that into a + b = 17 to make:(11 + b) + b = 1711 + 2b = 17So b = 3If b = 3, then a + 3 = 17 , so a = 14, 3 + c = 25, so c = 22So a=14, b=3, c=22, so a+b+c = 14+3+22 = 39

16.5

To find this: You know (B+C) = 7. Therefore you know (A+A )= 21 - (B+C). Therefore 21-7 = 14. So now you know (A+A) = 14. So you divide (A+A)/2. This equals 7. Therefore A = 7.

Related questions

-11

-14 + c + 6 = -5-14 + c = -5 minus 6-14 + c = -11c = -11 minus -14c = -11 plus 14c = 3

c plus 8 equals 11; now subtract 8 from both sides, then c=3.

a+b = 17a+c = 36 ----> c = 36 - ab+c = 25 ----> c = 25 - bSo since both are c, we say36 - a = 25 -bFrom this : 11 = a - bLook at 1st eqn: a + b = 17Now we have: a - b = 11 ----> a = 11 + bSo we can substitute that into a + b = 17 to make:(11 + b) + b = 1711 + 2b = 17So b = 3If b = 3, then a + 3 = 17 , so a = 14, 3 + c = 25, so c = 22So a=14, b=3, c=22, so a+b+c = 14+3+22 = 39

The answer is 21 because if 21 is divided by 3 it equals 7 plus 4 equals 11.

2a + 2b = 26 2b + c = 22 ===> b = 11 - c/2 4c + 2b = 46 ===> b = 23 - 2c From the 2nd and 3rd equations: 11 - c/2 = 23 - 2c 22 - c = 46 - 4c 22 - 46 = -4c + c ===> -24 = -3c ===> c = 8 Substitute c=8 into the 3rd equation: b = 23 - 16 = 7 Substitute b=7 into the 1st equation: 2a + 14 = 26 2a = 12 ===> a = 6

A=8 B=4 C=14 Yes, I know I'm a genius. Mak - the all knowing one. MWAHAHAH!

a+b+c+d+e = 30 (i) c+e = 14 (ii) d+b = 1 (iii) a = 2b-1 (iv) a+c = 10 (v) By (i)-(ii)-(iii): a = 15 then, by (iv): b = 8 and by (v): c = -5 Also, b = 8 so by (iii): d = -7 and then by (i), e = 19

the answer is a

16.5

+/- 11

To find this: You know (B+C) = 7. Therefore you know (A+A )= 21 - (B+C). Therefore 21-7 = 14. So now you know (A+A) = 14. So you divide (A+A)/2. This equals 7. Therefore A = 7.